2018
DOI: 10.1007/s10552-018-1022-3
|View full text |Cite
|
Sign up to set email alerts
|

A cancer registry-based analysis on the non-white populations reveals a critical role of the female sex in early-onset melanoma

Abstract: Our results highlight the importance of gender as one of the melanoma risk factors beyond traditional UV radiation, which warrants further investigation and may provide a base for an improved prevention strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…We and others have previously reported that the unadjusted age-specific female to male IRRs exhibited a spiked difference around the age of 20–24 years in both the white and non-white populations [4,26], with non-whites showing a slight shift of age from 20–39 years [26]. This trend was, again, observed in three out of four major body sites in whites, and all four body sites in non-whites (Figure 2A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously reported that the unadjusted age-specific female to male IRRs exhibited a spiked difference around the age of 20–24 years in both the white and non-white populations [4,26], with non-whites showing a slight shift of age from 20–39 years [26]. This trend was, again, observed in three out of four major body sites in whites, and all four body sites in non-whites (Figure 2A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Age-standardized rates were adjusted to the US 2000 standard population. The rate ratios were calculated using female incidence rates divided by male rates as previously described [26]. The 95% confidence intervals of the rate ratios were calculated by Stata (version 13.1, StataCorp LLC, College Station, Texas, USA) [27].…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study found that female sex may be an independent risk factor for early-onset melanoma, independent of ultraviolet radiation exposure (Liu-Smith and Ziogas, 2017). Furthermore, nonwhite female subjects aged < 40 years were found to have an elevated risk of melanoma compared with male subjects of the same age, which suggests that tanning bed usage alone may not explain this increased risk (Yuan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The GENEVA samples were potentially able to call all potential SNPs, and therefore, this might be another reason that we could not replicate the findings. Nevertheless, as demonstrated in our series of publications [2][3][4]7,81], the gender difference in melanoma incidence is significant but not yet fully explained. Meanwhile, studies on hormone impact on melanoma are still ongoing in our lab and other research groups.…”
Section: Discussionmentioning
confidence: 69%